The Constraints of The Teachers in The Implementation of 2013 Curriculum At SMP Negeri 1 Dullah, Maluku - Umar Rahaded; Hendro Widodo (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2018)
This study was aimed to describe the constraints of the teachers in the implementation of the 2013 curriculum. This study was descriptive research. The subjects were teachers in SMP Negeri 1 Dullah. The data were analyzed using the descriptive analysis technique. The data were collected using interviews, observation and documentation. The validity of the data was obtained through the method triangulation. The results of the study show that the constraints experienced by the teacher include making learning media, understanding teachers, integrating inter-learning lessons in thematic learning, and mastering information technology. While other constraints originating from the government include the distribution of books, assessment, teacher administration, time allocation, socialization, guidelines for implementing the curriculum, and learning activities in student books.